Integrating a brief substance abuse awareness intervention into a couples treatment program for intimate partner violence - McCollum, Eric E.; Stith, Sandra M.; Strachman Miller, Marjorie; Ratcliffe, G. Cole (My University, 2012)
Substance abuse (SA) and intimate partner violence (IPV) frequently co-occur providing challenges to researchers and treatment professionals alike. Researchers have struggled to understand the nature of the relationship between these two difficult issues. Are they wholly un-related, indirectly related, or is there a causal relationship between the two? Treatment professionals face the dilemma of how to provide treatment to clients who abuse substances and who are violent with heir intimate others. Most treatment for these two disorders is provided separately with varying degrees of effort to coordinate them. Models of combined treatment are few, and none address couples in which both partners are violent and/or abuse substances. In this paper, we briefly review the literature on SA and IPV and then describe a brief substance abuse awareness intervention, based on Motivational Interviewing, that we have integrated into our conjoint couples treatment model for IPV.
Including a brief substance-abuse motivational intervention in a couples treatment program for intimate partner violence
Keywords: Substance abuse; Domestic violence; Intimate partner violence; Couple therapy